Bridging Legal Reform And Climate Action: Strengthening Rule Of Law To Advance SDG 13 In The Global South - Muh ibnu sholeh; Siti Fatinnah Binti Ab Rahman (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
Developing countries face significant structural and institutional challenges in achieving Sustainable Development Goal (SDG) 13, which calls for urgent action to combat climate change and its impacts. This article explores the critical link between legal reform and climate action, emphasizing the role of the rule of law as a transformative instrument to accelerate the implementation of equitable and sustainable climate policies. Using a juridical-normative approach combined with international legal policy analysis, the study examines how legal instruments can be adapted and strengthened to enhance the systemic capacity of developing nations in responding to the climate crisis. The findings reveal that countries in the Global South that pursue progressive legal reforms particularly in the areas of environmental protection and resource governance are demonstrably more effective in implementing climate strategies. These reforms, grounded in principles of transparency, public participation, and ecological justice, contribute to institutional resilience and legal accountability. The study argues for a greater integration between national legal frameworks and global climate commitments, in order to establish an inclusive and responsive legal ecosystem that enables sustainable development and climate resilience. Strengthening the rule of law thus emerges as a foundational strategy for bridging the gap between climate pledges and practical implementation